The Reduced Oligomerization of MAVS Mediated by ROS Enhances the Cellular Radioresistance. (4th March 2020) - Du, Yarong; Pan, Dong; Jia, Rong; Chen, Yaxiong; Jia, Cong; Wang, Jufang; Hu, Burong
Abstract : Although the mitochondrial antiviral signaling protein (MAVS), located in the mitochondrial outmembrane, is believed to be a signaling adaptor with antiviral feature firstly, it has been shown that suppression of MAVS enhanced radioresistance. The mechanisms underlying this radioresistance remain unclear. Our current study demonstrated that knockdown of MAVS alleviated the radiation-induced mitochondrial dysfunction (mitochondrial membrane potential disruption and ATP production), downregulated the expressions of proapoptotic proteins, and reduced the generation of ROS in cells after irradiation. Furthermore, inhibition of mitochondrial ROS by the mitochondria-targeted antioxidant MitoQ reduced amounts of oligomerized MAVS after irradiation compared with the control group and also prevented the incidence of MN and increased the survival fraction of normal A549 cells after irradiation. To our knowledge, it is the first report to indicate that MAVS, an innate immune signaling molecule, is involved in radiation response via its oligomerization mediated by radiation-induced ROS, which may be a potential target for the precise radiotherapy or radioprotection.